Characterization of an OrtT-like toxin of Salmonella enterica serovar Houten - Barbosa, Luiz Carlos Bertucci (Braz J Microbiol, 2019)
The Escherichia coli GhoT/GhoS system is a type V toxin–antitoxin system in which the antitoxin GhoS cleaves the GhoT mRNA, controlling its translation. GhoT is a small hydrophobic protein that damages bacterial membranes. OrtT is a GhoT-like toxin, but it apparently lacks a corresponding antitoxin and serves a different physiologic role. Using a profile hidden Markov model approach, a Salmonella enterica serovar Houten genome was screened to obtain homologs of GhoT/OrtT. We only found one protein (referred to here as OrtT-Sal) that shared more sequence identity with OrtT than GhoT. The chromosomal region around the coding sequence of OrtT-Sal suggests that it is an orphan toxin and can be under RpoH activation. To study OrtT-Sal, we chemically synthesized and expressed in E. coli the whole toxin and its N- and C-terminal regions (OrtT-Sal(1–29) and OrtT-Sal(29–57), respectively). Our findings have shown that the overproduction of the polypeptides resulted in severe growth inhibition and cell lysis. Using circular dichroism, we found that OrtT-Sal, OrtT-Sal(1–29), and OrtT-Sal(29–57) form an alpha-helical structure in the presence of SDS micelles or TFE. Finally, using carboxyfluorescein-loaded lipid vesicles, we determined that the polypeptides damage lipid membrane directly. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s42770-019-00085-3) contains supplementary material, which is available to authorized users.